2020
DOI: 10.1186/s12879-020-05659-3
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide and fluoroquinolone associated mutations in Mycoplasma genitalium in a retrospective study of male and female patients seeking care at a STI Clinic in Guangzhou, China, 2016-2018

Abstract: Background Antimicrobial resistance in M. genitalium is a growing clinical problem. We investigated the mutations associated with macrolide and fluoroquinolone resistance, two commonly used medical regimens for treatment in China. Our aim is to analyze the prevalence and diversity of mutations among M. genitalium-positive clinical specimens in Guangzhou, south China. Methods A total of 154 stored M. genitalium positive specimens from men and women … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“… 22 Yet, Asian origin has not been identified as a risk factor before. Nonetheless, the prevalence of QRAM in Japan, 11 Singapore 24 and China 25 is much higher than in Europe. Travelling to a country with a high prevalence of QRAM or having sex with a person from such a country might be a risk factor for QRAM.…”
Section: Discussionmentioning
confidence: 92%
“… 22 Yet, Asian origin has not been identified as a risk factor before. Nonetheless, the prevalence of QRAM in Japan, 11 Singapore 24 and China 25 is much higher than in Europe. Travelling to a country with a high prevalence of QRAM or having sex with a person from such a country might be a risk factor for QRAM.…”
Section: Discussionmentioning
confidence: 92%
“…The U.S. Food and Drug Administration (FDA) approved such testing in early 2019 [51][52][53]. Unfortunately, recent research has identified various genetic mutations in M. genitalium that result in antimicrobial resistance (AMR) [54][55][56][57]. The prevalence of mutations in the 23S rRNA gene (which allow for macrolide resistance) seems to be increasing worldwide, and more rapidly than topoisomerase/gyrase mutations (parC/gyrA) (which provide fluoroquinolone resistance) [58,59].…”
Section: Mycoplasma Genitaliummentioning
confidence: 99%
“…In Japan, the prevalence increased from 4.8 % before 2010–28.7 % in 2016–2017. In contrast, the prevalence was the lowest in Europe (2.8 %) [10–12]. In addition, M.…”
Section: Full-textmentioning
confidence: 99%